2004
DOI: 10.1159/000077337
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Predisposition to Neurological Symptoms in Lacunar Infarction

Abstract: Objective: Lacunar infarction is a unique stroke entity with characteristic symptoms. However, it is often silent clinically. The possible genetic predisposition to symptoms of lacunar infarction was investigated. Methods: One-hundred and fifty-one patients with lacunar stroke were consecutively recruited. Lacunar stroke was diagnosed based on both neurological symptoms and lacunar lesion(s), demonstrated by MRI, that were responsible for the symptoms. One-hundred and fifty control subjects with MRI-proven lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…This is supported by another MRI-based twin study which reported much higher concordance rates of MBL in monozygotic compared with dizygotic twin pairs, and in addition, revealed a MBL concordance rate of 38% among dizygotic twins, a result similar to our prevalence rate of 42% in affected sibs [24]. Moreover, recent association studies provide evidence for genetic susceptibility factors in lacunar infarction [25, 26]. However, given the lack of other studies focused on cerebral microangiopathy in siblings and the relatively small number of sib pairs in the present study, our results need to be confirmed in larger cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…This is supported by another MRI-based twin study which reported much higher concordance rates of MBL in monozygotic compared with dizygotic twin pairs, and in addition, revealed a MBL concordance rate of 38% among dizygotic twins, a result similar to our prevalence rate of 42% in affected sibs [24]. Moreover, recent association studies provide evidence for genetic susceptibility factors in lacunar infarction [25, 26]. However, given the lack of other studies focused on cerebral microangiopathy in siblings and the relatively small number of sib pairs in the present study, our results need to be confirmed in larger cohorts.…”
Section: Discussionsupporting
confidence: 90%
“…Only the intron 4ab genotype of the eNOS gene was associated with isolated lacunar infarction and the AGT-20C allele may be a risk factor for leukoaraiosis [24,25,26,27]. Other studies have reported a strong association of the angiotensin-converting-enzyme genotype to lacunar stroke [28, 29] as well as a –174G/C polymorphism of interleukin 6 [30, 31] and a gene variant of α 1 -antichymotrypsin – a plasma protease inhibitor [32]. …”
Section: Discussionmentioning
confidence: 99%
“…One form of migraine, familiar hemiplegic migraine, is known as a genetic disease [65]. Epidemiological surveys found that first-degree relatives have a higher risk to develop a migraine than people with a negative family history [66]. The angiotensin-converting enzyme gene deletion polymorphism (ACE-DD) and the methylenetetrahydrofolate reductase (MTHFR) C677-TT polymorphism are genetic factors that increase susceptibility to oxidative stress, endothelial dysfunction and stroke [16].…”
Section: Migrainous Infarctionmentioning
confidence: 99%